2009
DOI: 10.1063/1.3186075
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen passivation of vacancy defects in metal-nitride gated HfO2/SiO2/Si devices

Abstract: We show that oxygen can be diffused through thin TiN layers to correct flatband voltage offsets in HfO2/SiO2/Si structures, achieving nearly band-edge capacitance voltage characteristics without undue growth of parasitic SiO2. Photoemission reveals that the TiN remains conductive despite mild oxidation, although over-oxidation results in insulating layers. Secondary ionization mass spectroscopy of samples treated with isotopically labeled O18 was used to assess how much oxygen is required to fully passivate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…It is worth mentioning that our device data has shown the presence of oxygen in TiN. 39 Further, we note from Table II that the presence of Al interstitial at the interface lowers the EWF, a behaviour similar to O vacancy. Thus, Al interstitial or O vacancies at the HfO 2 / TiN interface may be good for nFET EWF engineering, whereas O in TiN bulk may be good for pFET EWF engineering.…”
Section: Effective Work Function Engineeringmentioning
confidence: 55%
See 1 more Smart Citation
“…It is worth mentioning that our device data has shown the presence of oxygen in TiN. 39 Further, we note from Table II that the presence of Al interstitial at the interface lowers the EWF, a behaviour similar to O vacancy. Thus, Al interstitial or O vacancies at the HfO 2 / TiN interface may be good for nFET EWF engineering, whereas O in TiN bulk may be good for pFET EWF engineering.…”
Section: Effective Work Function Engineeringmentioning
confidence: 55%
“…This barrier can be overcome only at high processing temperature. 39 We have investigated the impact of these point defects at the HfO 2 /TiN interface as well as in bulk TiN on the EWF. We have shown that the presence of Al interstitial or O vacancy at HfO 2 /TiN interface gives lower EWF compared to defect-free interface.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of the TaN can change the work function of the metal gate and contribute to the observed V FB shift. 10 Nevertheless, it is evident the Ta oxidation is taking place at the upper part of the TaN layer and not at the TaN/dielectric interface, suggesting that the TaN work function is not being modified near the TaN/ dielectric interface. Furthermore, the filling of vacancies due to O diffusion into the bulk of TaN and any bond dipole this may produce will be screened by TaN metal and is not expected to shift the V FB by much.…”
Section: à2mentioning
confidence: 97%
“…Gate-last TiN/HfO 2 band edge effective work functions using low-temperature anneals and selective cladding to control interface composition Recent publications in advanced high-k and metal gate (HK/MG) stack technology [1][2][3][4][5][6][7][8] demonstrate the division between gate-first and gate-last strategies employed by those in the field. Gate-first HK/MG technologies have been presented for the 45 nm (Ref.…”
mentioning
confidence: 99%